Leader-Follower Exchange Quality: The Role of Personal and Interpersonal Attributes - Phillips, Antoinette S.; Bedeian, Arthur G. (Academy of Management Journal, 1994)
A field study of 84 registered nurses and their supervisors revealed that leaders' perceptions of leader-follower attitudinal similarity and follower extraversion were positively related to the quality of leader-follower exchanges. Neither followers' locus of control nor growth need strength was found to be significantly correlated with the quality of the exchange between leaders and followers.